2010
DOI: 10.19030/ajbe.v3i3.404
|View full text |Cite
|
Sign up to set email alerts
|

Clicking Our Way To Class Discussion

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="color: #0d0d0d; font-size: 10pt;"><span style="font-family: Times New Roman;">The goal of this research project is to investigate whether the use of a personal response system (&ldquo;clickers&rdquo;) in the classroom increases student participation and discussion and its impact on the quality of the discussion in undergraduate accounting courses.<span style="mso-spacerun: yes;">&nbsp; <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Instead of finding improvement in participation, some research (i.e., Carnaghan and Webb, 2007), in fact, found that student participation actually decreased, particularly when most students answer the questions correctly. A similar finding was noted by other researchers (Morse et al, 2010), where either a modest increase or no enhancement in participation was found when an SRS was used to ask a discussion question at the start of each lecture.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Instead of finding improvement in participation, some research (i.e., Carnaghan and Webb, 2007), in fact, found that student participation actually decreased, particularly when most students answer the questions correctly. A similar finding was noted by other researchers (Morse et al, 2010), where either a modest increase or no enhancement in participation was found when an SRS was used to ask a discussion question at the start of each lecture.…”
Section: Discussionsupporting
confidence: 87%
“…However, the clickers cannot be proved equally advantageous for all the students in the class. Bain and Przybyla (2009) [2] Carnaghan and Webb (2007); Morse et al (2010) Learning Experience Enhances student learning experience Humphries and Whelan (2009); Nelson and Hauck (2008); Sprague and Dahl (2010); Stagg and Lane (2010) The use of clickers alone cannot work as a panacea for improved learning Bain and Przybyla (2009); Koppel and Berenson (2008) Performance Enhanced student performance Bain and Przybyla (2009); Hedgcock and Rouwenhorst (2014); Hoanca (2013) The use of clickers alone does not increase performance Blasco-Arcas et al (2013); Marshall and Varnon (2012) Feedback Clicker use allows the learners to get instant feedback Hedgcock and Rouwenhorst (2014); Koppel and Berenson (2008); Lincoln (2007); Nelson and Hauck (2008); Thoms and Williams (2010) Not of much use to those who [1] tend to get everything right all the time or [2] are not interested in responding to questions or perform worst every time Lincoln (2007)…”
Section: Satisfactionmentioning
confidence: 99%
“…The literature is split as to whether or not the use of ARS substantially improves student grades. Pre-lecture and post-test scores may correlate more to question writing skills than to the actual use of clicker questions (Filer, 2010;Lantz, 2010;Morse, Ruggieri, & Whelan-Berry, 2010;Nightingale, 2010;Porter & Tousman, 2010;Smith & Rosenkoetter, 2009;Zurmehly & Leadingham, 2008). Cunningham (2008) used ARS to follow the progress of 840 students.…”
Section: The Audience Sees and Answers A Questionmentioning
confidence: 99%
“…In this sense, many efforts are ongoing on clicker use in higher education settings (Carnaghan & Webb, 2007;Nelson & Hauck, 2008;Morse et al, 2010;Carla, Thomas, Thomas, & Philip, 2011). However, in regard to educational levels, Mun et al (2009) suggested that more research would facilitate better understanding concerning how clickers affect student participation in K-12 levels; hence, the period of clicker use may also provide crucial hints for their efficacy in EFL courses.…”
Section: Clickers In Efl Classroomsmentioning
confidence: 99%